Technical Efficiency of Lobster (Panulirus sp) Farming in East Lombok Regency - Muhammad Nursan; Syarif Husni; M. Yusuf; Aeko Fria Utama FR; Ni Made Nike Zeamita Widiyanti (Jurnal Biologi Tropis, 2021)
East Lombok Regency is one of the centers for the development of aquaculture and the largest lobster seed producer in Indonesia. However, in terms of productivity, lobster cultivation is still relatively low due to the less optimal use of production factors and management in carrying out lobster rearing cultivation. The purpose of this study was to analyze the factors that affect the production of lobster rearing aquaculture and to analyze the level of technical efficiency and the factors that influence the technical inefficiency of lobster rearing aquaculture in East Lombok Regency. Descriptive research method was selected in this research. Cross section data was collected using a survey technique on 40 respondents who were selected by simple random sampling. The collected data was then analyzed using the Cobb-Douglas Stochastic Frontier production function with the Maximum Likelihood Estimator (MLE) method. The results showed that the production of lobster rearing aquaculture in East Lombok Regency was significantly influenced at the alpha level 5% by the variables of the number of cages, feed, number of family dependents and dummy species. The level of technical efficiency of lobster rearing cultivation is classified as efficient with a technical efficiency value of 0.94. Then the factors that affect the inefficiency of lobster rearing business in East Lombok Regency include age, education level and training dummy.